The animator’s proposal - Ramlie, Mohd Khairulnizam; Ramli, Ishak; Ab Gani, Muhammad Abdul Aziz; Mohammad Ali, Irwan (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
The current 2D animation course requires students to understand its history, the latest technologies, and the animation development process within a 14-week. However, 40% of the semester is allocated to pre-production activities such as idea generation, storyline structuring, scriptwriting, and visual research. This allocation leaves students with insufficient time for technical tutorials and the creation of high-quality 2D animations. The 2D Animation Proposal Development Model (2DTAP) is an educational innovation leveraging AI technology, particularly ChatGPT, integrated with a systematic guideline. This model accelerates and simplifies the pre-production process, enabling students to focus on mastering production techniques. By combining AI technology with clear guidelines, 2DTAP reduces cognitive load, enhances learning effectiveness, and ensures students produce high-quality animation projects. The novelty of 2DTAP lies in its unique integration approach, merging AI with structured learning guidance to achieve relevant pre-production outcomes suitable to students' skill levels. Studies reveal that 2DTAP significantly improves learning quality and the final project outcomes of students, highlighting its potential to enhance the competitiveness of graduates in the animation industry.